Citrus exocortis viroid and Hop Stunt viroid Doubly infecting grapevines in Brazil - Eiras,Marcelo (2006)
Viroids, non-protein-coding small (246-401 nt) circular single-stranded RNAs with autonomous replication, are currently classified into two families. Within the family Pospiviroidae, Citrus exocortis viroid (CEVd) belongs to the genus Pospiviroid while Hop stunt viroid (HSVd) is the single member of the genus Hostuviroid. These pathogens are distributed worldwide and infect a large number of hosts. In Brazil, isolates of CEVd and HSVd have been detected in both citrus and grapevine. To characterize and study the genetic variability of these viroids, total RNA from leaves of grapevine Vitis vinifera 'Cabernet Sauvignon' and V. labrusca 'Niagara Rosada' from Bento Gonçalves, RS, was used as a template for RT-PCR amplification with specific primers for the five viroids described infecting grapevines [HSVd, CEVd, Grapevine yellow speckle viroid 1 (GYSVd-1), Grapevine yellow speckle viroid 2 (GYSVd-2) and Australian grapevine viroid (AGVd)]. Leaf samples of Citrus medica infected with CEVd from São Paulo were also analyzed. The resulting products were separated by agarose gel electrophoresis and DNA fragments of the expected size were eluted, cloned and sequenced. The grapevine samples analyzed were doubly infected by CEVd and HSVd. A phylogenetic analysis showed that the Brazilian grapevine HSVd variants clustered with other grapevine HSVd variants, forming a specific group separated from citrus variants, whereas the Brazilian CEVd variants clustered with other citrus and grapevine variants.